Perbedaan Pendapat Ulama tentang Pengguguran Kandungan Sebelum dan Sesudah 120 hari dalam Perspektif Fiqih Islam - Akmal Kautsar; Ucu Ucu; Naswa Khairunisa (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
This study discusses the differences in opinion among Islamic scholars regarding the law of abortion before and after 120 days of pregnancy from the perspective of Islamic jurisprudence. The issue of abortion is continuously debated because it relates to aspects of religion, morality, health, and the right to life of the fetus. In Islam, scholars agree that abortion after the breath of the soul at 120 days is forbidden except in emergencies to save the mother's life. However, before 120 days, there are differences of opinion among scholars of various schools of thought regarding the permissibility of abortion. This study uses a library research method (literature research) with a normative approach through analysis of the Qur'an, hadith, fiqh books, fatwas of scholars, and relevant scientific journals. Previous research shows that the Hanafi school tends to provide leniency before 120 days under certain conditions, while some Shafi'iyah and Malikiyah scholars are stricter in prohibiting abortion from early pregnancy. The research results show that differences of opinion among Islamic scholars are influenced by differing understandings of the human creation process, the timing of the soul's instillation, and the use of the legal istinbath method. Despite these differing views, most scholars maintain that protecting the soul (ḥifẓ an-nafs) is the primary objective of Islamic law. Therefore, abortion is only permissible in emergencies that truly threaten the mother's life. Keywords: Abortion, Islamic Jurisprudence, 120 Days, Fetus, Islamic Law